Fusarium head blight: emergence, impacts on wheat production and management in Ethiopia and beyond - Horo, Jemal Tola; He, Xinyao; Danu, Kitessa Gutu; Hei, Netsanet Bacha; Megerssa, Shitaye Homma; Zhang, Xu; Singh, Pawan Kumar (Frontiers in Agronomy, 2026)
Fusarium head blight (FHB), caused predominantly by Fusarium graminearum species complex, is a re-emerging and highly damaging disease affecting wheat production in Ethiopia and other wheat-growing countries in the Sub-Saharan Africa (SSA). The disease results in a significant reduction of yield and contaminates wheat grain by producing mycotoxins, particularly deoxynivalenol (DON), which has adverse effects on human and animal health. This article examines the disease emergence, its impact on the national economy, and solutions for managing it in SSA. FHB disease is highly prevalent and can cause grain yield losses of over 50% in the SSA, especially in Ethiopia. Globally, it is recognized as a highly challenging wheat disease to manage, which necessitates an integrated disease management approach including host resistance, cultural, biological, and chemical control strategies. Implementing crop rotation with non-host crops, such as soybeans, and effectively managing crop residue are essential cultural practices that greatly decrease the occurrence and intensity of FHB. Studies revealed that there is no wheat genotype immune to wheat FHB disease. However, research evidences show that utilizing moderately resistant wheat varieties in combination with other control methods could limit the development of the disease effectively. Although there have been limited fungicide efficacy testing conducted in SSA, the use of multiple triazole-based chemical fungicides, such as prothioconazole, tebuconazole, and propiconazole, either individually or in combination, are suggested as an effective method for controlling FHB in wheat in other nations, such as the United States, Europe, and China. The only fungicides currently available in Ethiopia are Fuzaro 400 SC (containing prothioconazole and tebuconazole) and Natura 250 EW (containing tebuconazole). In general, SSA has made little effort to develop FHB management strategies, resulting in lack of information regarding the disease control strategies in the region. Hence, it is crucial to immediately develop an integrated FHB disease management strategy and improve disease monitoring, identification, and forecasting. Improving the success of FHB management relies heavily on fostering awareness and education among wheat growers, as well as promoting regional and international collaboration. The findings of this review indicate that the development and implementation of an effective integrated management strategy for wheat FHB will substantially enhance regional production and productivity. Furthermore, it would provide considerable support to national wheat initiatives aimed at ensuring food security and safety in SSA, with specific relevance to Ethiopia.